Age and Work Performance in Nonmanagerial Jobs: The Effects of Experience and Occupational Type - Avolio, Bruce J.; Waldman, David A.; McDaniel, Michael A. (Academy of Management Journal, 1990)
This study examined the relative explanatory powers of age and total years of experience in an occupation for predicting supervisory ratings of work performance. As predicted, results indicated that experience was a better predictor of performance than age. A breakdown of jobs into five occupational groupings revealed a moderating effect for occupational type. Findings also showed that age and experience exhibit nonlinear relationships with performance.